Science, technology and reparations exploitation and plunder in postwar Germany - Gimbel, John 1922-1992 (Stanford Univ. Press, 1990)
John Gimbel: Science, Technology and Reparations. Exploitation and Plunder in Postwar Germany. Stanford University Press, Stanford 1990. 280 Seiten, 29,50 Dollar